CHANGING PARADIGM OF GEOGRAPHY LEARNING FROM INDIVIDUAL BASED TO TEAM BASED GEOGRAPHIC LEARNING PARADIGM - Hendra Hendra (Universitas Negeri Makassar, 2021)
The team-based geography learning paradigm is very important in 21st century learning. Team-based geography learning is able to explore and overcome the limited ability of teachers in material that they do not master. There are problems in changing geography learning from individual to team-based paradigms. The understanding of students and teachers is still constructed with the individual-based geography learning paradigm. There is no willingness to accept the shift in the paradigm of team-based geography learning. The concept of team-based geography learning has not been able to be understood and mastered holistically. Efforts to change the paradigm of individual-based geography learning towards team-based learning paradigms. 1) Unfreezing geography learning paradigm 2) Geography learning paradigm movement 3) Refreezing geography learning paradigm